Decoding Preferences: Unraveling Factors Influencing the Selection of Islamic Banking in the Minas District Community - Safardilah Arby; Anita Priantina (Journal of Islamic Civilization, 2023)
Despite the economic growth in the Minas district, the development of Islamic banks remains under-researched, making it an interesting topic for investigation. This study aims to assess the impact of knowledge, religiosity and community attitudes on savings interest in Islamic banks. The variables considered are knowledge (X1), religiosity (X2), attitude (X3) and savings interest rate (Y). Using a quantitative descriptive approach with Structural Equation Modelling Partial Least Squares (SEM PLS), primary data were collected from questionnaires targeting individuals aged 15 years and above in Minas District, Siak Regency, Riau Province. The results show that knowledge and religiosity have a positive and significant influence on Islamic banks, while attitude shows no significant influence. These findings provide crucial insights into the determinants of Islamic banking services at the local level and suggest that Islamic banks and stakeholders should develop more effective marketing and educational strategies. These strategies aim to improve community knowledge, religiosity and attitudes towards Shariah finance and ultimately promote interest in saving, especially in the Minas district.